TRADISI PERJODOHAN BERDASARKAN WETON DAN PASARAN DALAM PRESPEKTIF MAQASHID AL-SYAR’IYYAH - Ubaidillah, M. Burhanuddin; Cindi Ameliana (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2025)
Primbon, a form of Javanese local wisdom, continues to be widely used in determining auspicious days, particularly in the context of marriage. This tradition remains deeply rooted in Javanese society, especially through calculations based on primbon prior to wedding ceremonies. In Javanese belief, a life partner (jodoh) is considered one of life’s great mysteries, along with destiny (pesthi) and divine calling (wahyu), all of which are believed to be partially concealed by God. To attain these, specific calculations or petungan are employed. Some Javanese use petungan merely as a means to find a potential spouse, while others integrate it into mystical practices, often through spiritual disciplines such as tirakat, which may be viewed as parallel to Islamic practices like tahajjud or istikharah prayers in seeking divine guidance for marital decisions. Special considerations when choosing a life partner—such as bibit (lineage), bobot (character), and bebet (social standing)—are crucial as they significantly impact the future of the marriage. This article focuses on the tradition of matchmaking based on weton and pasaran (Javanese calendrical elements) from the perspective of Maqāṣid alSharī‘ah. It begins with the conceptual foundations of weton and pasaran, explores the tradition of matchmaking based on these elements, analyzes the calculation methods for prospective couples, and examines solutions for mismatched outcomes. Ultimately, it aims to uncover the essence of matchmaking through weton and pasaran within the framework of Maqāṣid alSharī‘ah.